PEMBENTUKAN PAPUA SELATAN SEBAGAI PROVINSI BARU DI INDONESIA THE ESTABLISHMENT OF SOUTH PAPUA AS A NEW PROVINCE IN INDONESIA: The Establishment of South Papua as a New Province in Indonesia - Armani, Mutiara Ayu; Primananda, Eko (AMICUS CURIAE, 2024)
Regional governments have the right to determine regional policies in order to realize the implementation of government affairs which fall under regional authority and are obliged to be guided by the norms, standards, procedures and criteria established by the central government. The issues discussed in this journal are what are the basis and conditions for consideration in determining South Papua as a new province in Indonesia and whether the determination of South Papua as a new province in Indonesia is in accordance with Law Number 23 of 2014 concerning Regional Government. This journal is descriptive normative legal research, with literature studies and interviews as well as deductive conclusion drawing. The secondary data obtained was processed qualitatively. Based on the results of research that: The formation of a new province in Indonesia must meet regional administrative, technical and physical requirements as regulated in Law Number 23 of 2014 concerning Regional Government, however, South Papua Province has special autonomous authority in determining to become a new province in Indonesia . The formation of the Papua Province contained inconsistencies in the regulations contained in Law Number 23 of 2014 concerning Regional Government and Law Number 14 of 2022 concerning the Establishment of the South Papua Province.